A study of studio environment on students’ project outcome / Akma Suhaila Md Noor...[et al.] - Md Noor, Akma Suhaila; Shaharudin, Haszlin; Ahmad, Mohamad Azroll; Bonollo, Ellivio; Wan Omar, Wan Noor Faaizah (Universiti Teknologi MARA, Kedah, 2020)
Teaching and learning the Industrial Design course in a university is usually conducted in a design studio, a place that develops and implements the assigned project work. However, design studios in the local universities still lack facilities and features. By saying so, we refer to outdated, imprecise and uncomfortable crafting tools, and environment. Thus, this research will investigate the studio-based design education environment from the viewpoint of Industrial Design inputs, such as cultural influences, facilities and functional parameters. Previous study has indicated that bad studio environment impacts the quality of a student’s project outcome. Limitation of space in the studio is an accurate example. Hence, by referring to the issues of the studio space including dull and less than encouraging environment, students are less compelled to devote their time in order to complete their tasks in the said enclosure. This project is set out to explore the factors of positive relations for learning in the arts and design studio environment where the students are able to carry out their ongoing project works. The importance of one to one teaching is still maintained by most faculty, especially in the arts and design studio environment where the students need open space and area for the completion of their project. The research objective is to find out the relationship between Industrial Design student’s department with the environment affecting the quality of their project outcomes.